Experimental investigation of pool boiling performance on hybrid surfaces - Al-Obaidy Ali M.H.; Fayyadh Ekhlas M.; Al-Dabagh Amer M. (FME Transactions)
The issue of excessive heat generation is present in the current electrical gadgets. Consequently, the task at hand is to devise a novel and effective cooling mechanism for them. To disperse the heat produced, the pool boiling method may provide a high heat transfer coefficient. The performance of the pool boiling process on the microchannel surfaces using saturated deionized water at atmospheric pressure has been experimentally investigated in this work. To examine the impact of coating deposited on the microchannel surface, ten surfaces were utilized. Four hybrid surfaces were manufactured: CNT (1 g), (CNT-GNPs (1:0.5) g), (CNT-GNPs (1:1) g), and (CNT-GNPs (1:1.5) g) on a rectangular micro-channel with 0.2 mm fin width, 0.4 mm channel depth and 0.8 mm channel width. Four plain surfaces were coated with the same material and concentrations mentioned above. And, for comparison, one microchannel surface of same dimension mentioned above and one bare plain surface were used. The results revealed that the hybrid surface with high concentration resulted in a higher performance. The maximum critical heat flux (CHF) augmentation is 125.5%, while the maximum heat transfer coefficient (HTC) enhancement is 312%. The outcomes are contrasted with previous work and have a good agreement.